Transformasi Ruang Publik Digital: Studi Kasus Komentar Netizen dalam Akun Curhat - Sekar Kasih, Arum Rindu; Maharani, Tisa (Universitas Muhammadiyah Surakarta, 2024)
In the current era of digital technology, the various digital platforms available in the form of social media mean that anyone can express as many things as they wish. Social media seems to be a personal